Early Breastfeeding Initiation: Impact of Socio-demographic, Knowledge and Social Support Factors - Syam, Azniah; Syafar, Muhammad; Amiruddin, Ridwan; Muzakkir; Darwis; Darmawan, Sri; Wahyuni, Sri; Mallongi, Anwar (Pakistan Journal of Nutrition, 2017)
Background and Objective: Early breastfeeding initiation in the 1st h after delivery seems unsuccessful. This study aimed to analyze the impact of socio-demographic, knowledge and social support factors toward the failure of early breastfeeding initiation. Materials and Methods: An observational prospective approach was used with 238 selected purposively pregnant women who were followed through delivery in South Sulawesi province. Field data were collected from April-December, 2015. Results: The study results showed that marital age (OR:1.88, 95% CI:1.07-3.31), place of delivery (OR:1.81, 95% CI:0.99-3.29) and midwife social support (OR:2.74, 95%:CI:1.62-4.66) were significant predictors of early breastfeeding initiation, whereas mother’s knowledge was not a significant predictive factor. Home birth was found to be significantly different from hospital birth. Conclusion: To make early breastfeeding initiation successful, it is necessary to combine good practices among an educated midwife, family and traditional birth attendant.